2007
DOI: 10.1002/jhet.5570440417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thiophene/phenylene co‐oligomers. V. Functionalization at molecular terminals toward optoelectronic device applications

Abstract: We report the synthesis of various thiophene/phenylene co‐oligomers with a total number of thiophene and benzene (phenylene) rings of 5 and 6 with various terminal groups. Those terminal groups have been chosen from among alkyl groups, methoxy groups, trifluoromethyl groups, and cyano groups. The molecular backbone of these compounds comprises phenyl‐ or biphenylyl‐capped thiophene (or oligothiophene) or an alternating co‐oligomer. The synthesis is based on either the Suzuki coupling reaction or the Negishi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 28 publications
3
72
0
Order By: Relevance
“…The synthetic root was slightly different as per a report by Katagiri et al [24]. We confirmed its structure by matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectroscopy (Perspective Biosystems, Voyager-DE PRO) and 1 H NMR (Bruker AVANCE 400)).…”
Section: Ac5-cf3 Was Synthesized By the Stille Coupling Reaction Of 4supporting
confidence: 76%
See 1 more Smart Citation
“…The synthetic root was slightly different as per a report by Katagiri et al [24]. We confirmed its structure by matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectroscopy (Perspective Biosystems, Voyager-DE PRO) and 1 H NMR (Bruker AVANCE 400)).…”
Section: Ac5-cf3 Was Synthesized By the Stille Coupling Reaction Of 4supporting
confidence: 76%
“…Note that Hotta et 4 al. recently reported the synthesis of the same material [24], formation of its crystal [25], the crystal structure and its field-effect transistors (FETs) [26]. However, Hotta et al reported that AC-CF3 single-crystal FETs showed n-type behavior and that the electron mobility of the FETs ranged from 1.6 to 3.9  10 −2 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The carrier mobility of the BP1T thin-film device is estimated at $10 À3 cm 2 V À1 s À1 for the normal p-channel DC operation. [15] We show in Figure 1b a schematic structure of the bottom-gate OLEFET device equipped with interdigitated electrodes of channel length L. (constant channel width 8 cm). The equivalent circuit is schematically shown in Figure 1c.…”
mentioning
confidence: 99%
“…We chose thiophene/phenylene co-oligomers (TPCOs), a newly occurring class of organic semiconductors [7,8]. The TPCOs are a series of compounds where thiophene and phenylene rings are hybridized at the molecular level with their various mutual arrangements.…”
Section: Introductionmentioning
confidence: 99%